Supporting open education practice: Reflective case studies from the University of Edinburgh - Lorna Campbell; Melissa Highton; Ewan McAndrew (Edutec, 2023)
This paper outlines the University of Edinburgh’s long-running strategic commitment to supporting sustainable open education practice (OEP) across the institution. It highlights how the University provides underpinning support and digital capability for OEP through central services working with policy makers, partners, students, and academics to support co-creation and active creation and use of open educational resources to develop digital literacy skills, transferable attributes, and learning enhancement. We present a range of case studies and exemplars of authentic OEP evidenced by reflective practice and semi-structured ethnographic interviews, including Wikimedia in the Curriculum initiatives, open textbook production, and co-creation of interdisciplinary STEM engagement resources for schools. The paper includes recommendations and considerations, providing a blueprint that other institutions can adopt to encourage sustainable OEP. Our experience shows that mainstreaming strategic support for OEP is key to ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all.